Viral Science Fiction: Five Types of Pandemic Fiction. Issue 1 (1st April 2022) - Milner, Andrew
Abstract : This article begins by explaining how sf as a genre has recently "gone viral." It then proceeds to a brief overview of the history of pandemic fiction, in the Bible, in the literary canon, and in genre sf. It concludes with a more detailed analysis of Albert Camus's La Peste (1947), which argues that this novel exhibits many characteristics Darko Suvin attributes to sf. The paper concludes that either La Peste is in fact sf or Suvin's famous definitions are themselves misconceived.